Preoperative serum-gamma-glutamyltransferase (GGT) does not represent an independent prognostic factor in a European cohort of patients with non-metastatic renal cell carcinoma. Issue 7 (10th April 2015) - Dalpiaz, Orietta; Pichler, Martin; Mrsic, Edvin; Reitz, Daniel; Krieger, Daniel; Venturino, Luca; Bezan, Angelika; Stojakovic, Tatjana; Pummer, Karl; Zigeuner, Richard; Hutterer, Georg C
Abstract : Aims: Increasing evidence suggests that the serum-gamma-glutamyltransferase (GGT) might correlate with tumour development and growth rates in various human cancer types. Thus, we decided to investigate the potential prognostic impact of the preoperatively assessed serum-GGT in a European cohort of patients with non-metastatic renal cell carcinoma (RCC). Methods: Clinicopathological data from 700 consecutive patients with non-metastatic RCC, operated between 2000 and 2010 at a single tertiary academic centre, were evaluated retrospectively. Preoperative serum-GGT was assessed 1 day before surgery. Patients were categorised using a serum-GGT cut-off value of 40 U/L according to a calculation by receiver operating curve analysis. Patients' cancer-specific survival (CSS), metastasis-free survival (MFS), as well as overall survival (OS) were assessed using the Kaplan-Meier method and Cox proportional models. Results: In univariate analysis, an elevated preoperative serum-GGT level (<40 U/L vs ≥40 U/L) was statistically significantly associated with a shorter MFS (HR=1.517, 95% CI 1.047 to 2.197, p=0.027). In multivariate analyses, pathological T-Stage (pT-1 vs pT-2–4, HR=2.065, 95% CI 1.665 to 2.560), tumour grade (G-1+G-2 vs G-3+G-4, HR=1.671, 95% CI 1.261 to 2.213), as well as the presence of histological tumour necrosis (No vs Yes, HR=2.031, 95% CI 1.355 to 3.046) were independent predictors of MFS in patients with RCC, whereas the preoperative serum-GGT failed to reach independent predictor status (<40 U/L vs ≥40 U/L, HR=1.156, 95% CI 0.791 to 1.690). No prognostic role for GGT in OS or CSS could be identified. Conclusions: In the cohort studied, patients with an elevated (≥40 U/L) preoperative serum-GGT had a subsequently shorter MFS only in univariate analysis. In contrast to previous studies, our data failed to demonstrate preoperatively assessed serum-GGT as an independent prognostic factor in patients with non-metastatic RCC.